2016
DOI: 10.3899/jrheum.151063
|View full text |Cite
|
Sign up to set email alerts
|

The Birmingham Vasculitis Activity Score as a Measure of Disease Activity in Patients with Giant Cell Arteritis

Abstract: Objective To evaluate the performance of the Birmingham Vasculitis Activity Score (BVAS) in the assessment of disease activity in giant cell arteritis (GCA). Methods Patients with GCA enrolled in a prospective, multicenter, longitudinal study with symptoms of active vasculitis during any visit were included. Spearman’s rank correlation was used to explore the association of the BVAS with other measures of disease activity. Results During a mean (SD) follow-up of 2.3 (1.6) years, symptoms of active GCA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 27 publications
(31 reference statements)
1
24
0
Order By: Relevance
“…The evaluation of disease activity and vascular damage of LVV is challenging [31][32][33]. Ocular manifestations and large artery complications were common damages in patients with GCA [34].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of disease activity and vascular damage of LVV is challenging [31][32][33]. Ocular manifestations and large artery complications were common damages in patients with GCA [34].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of a single tool, criteria used by an NIH group for active disease (8), the Birmingham Vasculitis Activity Score (BVAS)(9), the Disease Extent Index for Takayasu’s arteritis (DEI.Tak) (10), and the Indian Takayasu’s Arteritis Score 2010 (ITAS2010) (11) have been used in clinical research for TAK (1214). A similar disease-specific tool does not exist for GCA and a recent study lead by investigators within the OMERACT Vasculitis Working Group found BVAS to have limited utility in GCA (15). A combination of clinical symptoms, glucocorticoids dose or duration, and/or BVAS has been used in clinical trials of GCA (13, 1618).…”
Section: Methods/resultsmentioning
confidence: 99%
“…The evaluation of disease activity and vascular damage of LVV is challenging (29)(30)(31). Ocular manifestations and large-artery complications were common damage in patients with GCA (32).…”
Section: Discussionmentioning
confidence: 99%